Assessment of the quality evaluation of compounded fluconazole capsules marketed in the region of Araraquara (SP, Brazil) - Corrêa, Josilene Chaves Ruela [UNESP]; Vanzela, Nathália Maia [UNESP]; Silva, Taízia Dutra; Vianna-Soares, Cristina Duarte; Salgado, Hérida Regina Nunes [UNESP] (My University, 2014)
The quality control of drugs has an important role in public health, in ensuring the efficacy and safety of medicines. In the public health system, compounding pharmacies play a vital part. They provide medicines tailored to the individual patient, for example dermatological products and specific doses for children. Unfortunately, many cases of compounded products falling below the minimum quality standard have been reported in Brazil. In this study, the quality of compounded 150 mg fluconazole capsules was assessed and the results were compared with values stipulated in the Brazilian pharmacopoeia. The results suggest that, while it is certainly possible to prepare products meeting pharmacopoeial specifications, there are pharmacies where the quality control is deficient or nonexistent. Fluconazole is an important drug in combatting fungal infections. The use of fluconazole in dosage forms manufactured without high standards of quality control is strongly linked to treatment failure and cases of intoxication, as well as the emergence of resistant microorganisms. This highlights the urgent need for process improvement in compounding pharmacies. There are validated methods that can be successfully employed for routine quality control analysis that can be implemented by any compounding pharmacy.

O controle de qualidade de fármacos desempenha um papel importante na saúde pública ao garantir segurança e eficácia de medicamentos. No sistema de saúde pública, as farmácias magistrais também são importantes. Elas fornecem medicamentos personalizados como produtos dermatológicos e doses específicas para crianças. Infelizmente, muitos casos de produtos magistrais fabricados fora do padrão mínimo de qualidade têm sido relatados no Brasil. Neste trabalho, a qualidade das cápsulas magistrais de fluconazol 150 mg foi avaliada e os resultados foram comparados com os valores recomendados pela Farmacopeia Brasileira. Os resultados sugerem que é possível manipular produtos que satisfaçam as especificações farmacopeicas, mas estes ainda mostram que há farmácias magistrais onde o controle de qualidade é deficiente ou inexistente. O fluconazol é um fármaco importante no tratamento de infecções fúngicas. Seu uso como forma farmacêutica manipulada sem elevados padrões de qualidade é fortemente relacionado com a falha terapêutica e intoxicações, assim como o surgimento de microorganismos resistentes. Portanto, a necessidade de melhoria dos processos nas farmácias magistrais se torna mais enfático. Existem métodos validados que podem ser utilizados com sucesso para a análise de rotina de controle de qualidade e que podem ser implementados por qualquer farmácia de manipulação.
Avaliação da qualidade de cápsulas de fluconazol manipuladas comercializadas na região de Araraquara (SP, Brasil)
Keywords: Fluconazole; Compounded medicines; Quality control; Public health; Fluconazol; Medicamentos magistrais; Controle de qualidade; Saúde pública